2014
DOI: 10.1007/s10518-014-9711-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the cyclic capacity of beam-to-column dowel connections in precast industrial buildings

Abstract: The behaviour of precast systems depends on the performance of the specific connections between the precast elements. In European precast design practice, the most common type of connection between beams and columns is a dowel connection. Such connections are subject to the following types of potential failure mechanism: (a) local failure characterized by the simultaneous yielding of the dowel and crushing of the surrounding concrete, and (b) global failure, characterized by spalling of the concrete between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 6 publications
0
51
0
Order By: Relevance
“…The procedure was tested against the experimental results obtained within the SAFECAST procedure (Zoubek et al 2014a, b). Very good match with the experimental results was demonstrated.…”
Section: Capacity Of the Beam-column Connections With Dowels Placed Cmentioning
confidence: 87%
See 1 more Smart Citation
“…The procedure was tested against the experimental results obtained within the SAFECAST procedure (Zoubek et al 2014a, b). Very good match with the experimental results was demonstrated.…”
Section: Capacity Of the Beam-column Connections With Dowels Placed Cmentioning
confidence: 87%
“…The behaviour of this connection is now fully understood and the design formulas and the design methodology are provided. Note that the design procedure for the connection with the dowels close to the edge of the column was recently improved (Zoubek et al 2014a, b) and considerably modified in comparison with the formulas given in the Design guidelines. 6.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, prefabricated structures, whose components are normally precast in building factories and then transported to the site to install, are attracting more and more attentions both at home and abroad . It was revealed that the prefabricated structure has significant advantages of green environmental protection, high construction efficiency, and low human cost . Even so, application of the prefabricated structure in China is still restricted due to severe anti‐seismic requirements in most seismic areas.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the ground motion was quantified by the maximum horizontal peak ground acceleration, which was obtained from ShakeMaps. Some buildings might have two floors or intermediate floors in specific areas, typically along one of the two short edges, where offices are usually located.Modern seismic design codes require adequate structural ductility and compliance with capacity design, with particular regard to connections between precast members [20][21][22][23]. With reference to Italian buildings, mainly comprising low-rise to mid-rise masonry and RC structures, Rota et al [9] proposed typological fragility curves based on earthquake damage data collected in the past 30 years.…”
mentioning
confidence: 99%
“…Modern seismic design codes require adequate structural ductility and compliance with capacity design, with particular regard to connections between precast members [20][21][22][23]. However, up until 2005, the region struck by the Emilia earthquakes was not considered as a seismic area by building codes.…”
mentioning
confidence: 99%